Hubungan Faktor Pengetahuan, Motivasi dan Tingkat Pendidikan dengan Kepatuhan Pemberian Imunisasi BCG - Budi Kristanto; Ernis Oki Puspita Sari (KOSALA : Jurnal Ilmu Kesehatan, 2019)
Background: The Indonesian Ministry of Health (2016: 01) states that in Indonesia it is estimated that 1 million new TB cases (647 per 100,000 population) with 100,000 deaths (41 per 100,000 population). Data from the Central Java Provincial Health Office (2018), said that there were 103,840 TB cases estimated, only 44.33% (48,751 sufferers) reported, so that there were still 55,089 undiscovered patients. The results of the study prove that one effective prevention for tuberculosis is BCG immunization. Research purposes: This study aims to determine the relationship of factors of knowledge, motivation and education level with adherence to BCG immunization. Subject: All mothers who have children over 1 year old at Posyandu Karang Gading Village Tanon Subdistrict are 35 people. Method: This study uses observational analytic methods with a research design correlation with a cross sectional approach to determine the relationship of knowledge, motivation and education level with adherence to implementing BCG immunization. Data obtained by questionnaire, then tabulated and analyzed using SPSS 18 for Windows. Research result: The results of the analysis with SPSS 18 for Windows used Chi Square for the dependent variable level of knowledge p value: 0.655, motivation p value: 0.109, education level p value: 0.212. Conclusion: there is no relationship between the level of knowledge, motivation and level of education towards the compliance of mothers taking BCG immunization actions on their children. Keywords: knowledge, motivation, education level, compliance with BCG immunization